(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the systemic effect of strontium ranelate (SR) on peri-implant bone tissue. Thirty-six adult rats were divided into three experimental groups: sham (SHAM), ovariectomized (OVX) and ovariectomized rats treated with strontium ranelate (OVX-Sr). Strontium ranelate (625mg/kg) was administered by oral gavage on a daily basis. The implants were installed on the tibiae. The euthanasia occurred 42 and 60 days after the implants were installed, and the biomechanical (reverse torque); PCR-RT; histological; immunohistochemical; confocal microscopy and histometric analysis were performed. Quantitative data was subjected to statistical tests with significance level set at p<0.05. Significant increase in implant reverse torque in OVX-Sr was observed when compared to OVX. PCR analysis showed an increase in the genetic expression of the proteins responsible for bone formation in OVX-SR. In the histological analysis, SHAM and OVX-Sr showed a higher degree of maturation of peri-implant bone tissue. Ran-Sr presented higher immunolabeling for ALP and OPN proteins when compared to OVX. In the confocal microscopy, OVX-Sr there was good bone neoformation showed by incorporation of Alizarin red fluorochrome. The histometric analysis, bone implant contact (BIC) and neoformed bone area (NBA) presented statistically difference among all groups, and the Ran-Sr presented the highest BIC. Thus, strontium ranelate improves osseointegration and quality of neoformed bone tissue around implants in estrogen deficient rats.